First-in-human, double-blind, randomized phase 1b study of peptide immunotherapy IMCY-0098 in new-onset type 1 diabetes - Jean Van Rampelbergh; Peter Achenbach; Richard David Leslie; Mohammad Alhadj Ali; Colin Dayan; Bart Keymeulen; Katharine R. Owen; Martin Kindermans; Frédéric Parmentier; Vincent Carlier; Roxana R. Ahangarani; Evelien Gebruers; et al. (BMC Medicine, 2023)
Abstract Background Type 1 diabetes (T1D) is a CD4+ T cell-driven autoimmune disease characterized by the destruction of insulin-producing pancreatic β-cells by CD8+ T cells. Achieving glycemic targets in T1D remains challenging in clinical practice; new treatments aim to halt autoimmunity and prolong β-cell survival. IMCY-0098 is a peptide derived from human proinsulin that contains a thiol-disulfide oxidoreductase motif at the N-terminus and was developed to halt disease progression by promoting the specific elimination of pathogenic T cells. Methods This first-in-human, 24-week, double-blind phase 1b study evaluated the safety of three dosages of IMCY-0098 in adults diagnosed with T1D < 6 months before study start. Forty-one participants were randomized to receive four bi-weekly injections of placebo or increasing doses of IMCY-0098 (dose groups A/B/C received 50/150/450 μg for priming followed by three further administrations of 25/75/225 μg, respectively). Multiple T1D-related clinical parameters were also assessed to monitor disease progression and inform future development. Long-term follow-up to 48 weeks was also conducted in a subset of patients. Results Treatment with IMCY-0098 was well tolerated with no systemic reactions; a total of 315 adverse events (AEs) were reported in 40 patients (97.6%) and were related to study treatment in 29 patients (68.3%). AEs were generally mild; no AE led to discontinuation of the study or death. No significant decline in C-peptide was noted from baseline to Week 24 for dose A, B, C, or placebo (mean change − 0.108, − 0.041, − 0.040, and − 0.012, respectively), suggesting no disease progression. Conclusions Promising safety profile and preliminary clinical response data support the design of a phase 2 study of IMCY-0098 in patients with recent-onset T1D. Trial registration IMCY-T1D-001: ClinicalTrials.gov NCT03272269; EudraCT: 2016–003514-27; and IMCY-T1D-002: ClinicalTrials.gov NCT04190693; EudraCT: 2018–003728-35.